AGRO-BIOLOGICAL POTENTIAL AND ORIGIN OF NAVARRA WINTER TRITICALE VARIETY - Diordiieva, I. P.; Riabovol, Ia. S.; Riabovol, L. O. (Scientific Progress & Innovations, 2019)
The research results of creating new highly productive materials of winter triticale using spelt wheat (Triticum spelta L.) in the breeding process are presented in the article. The research was conducted during 2006–2015 at Uman National University of Horticulture. Spring triticale Khlibodar Kharkivskyi, winter triticale Rosivska 6 and samples of spelt wheat from the foot of the Carpathians were used as initial material for the research. Hybrid progeny F2-5 was analyzed for the manifestation of morphological characteristics and economically-valuable indices such as plant height, spike length and color, ear density, grain threshing out from the ear, the weight of 1000 grains, gluten content, protein content, and so on. Control testing was carried out during 2012–2015. The systematic method of plot placement was used for control variety testing. The accounting area of the plot was 10 m2. The experiment was conducted in four replications. State scientific- technical expert examination was carried out during 2015–2018 in 17 State regional centers of plant varieties expertise in different regions of Ukraine. The initial stage of the research was the hybridization of three-species Rosivska 6 winter triticale variety with spelt wheat and the following F1 hybrids crossing with Khlibodar Hharkivskyi spring triticale variety. While using multiple individual selection, sample 491 was selected among the progeny. This sample was analyzed in competition variety testing, where it significantly exceeded the average group standard as to the yield capacity (5.97 t/ha) and was not inferior in gluten content (21.7 %), the weight of 1000 grains (47.8 g). In 2015, sample 491 was transferred to the State scientifictechnic expert examination under the name of Navarra. During this period the variety average yield capacity in Polissia zone was 5.46 t/ha, 1.0 t/ha exceeding the average yield indices in the zone; in the Forest-Steppe the yield was 5.26 t/ha. The variety successfully combines high productivity with high grain quality (protein content − 13.1 %, the weight of 1000 grains − 48.6 g) and high resistance to unfavorable environmental factors. According to the results of State scientific -technical expert examination, Navarra variety was entered in the list of the State register of plant varieties, suitable for distribution in Ukraine in 2019, and recommended for cultivation in Polissia zone.